Revisiting Childhood-Onset Systemic Lupus Erythematosus - Pınar Özge Avar-Aydın; Hermine I. Brunner (AVES Yayincilik, 2024)
Childhood-onset systemic lupus erythematosus (cSLE) is a chronic autoimmune disease with a multisystemic involvement diagnosed during childhood. The disease is marked by the production of autoantibodies targeting self-antigens, often before symptoms emerge. The presentation, clinical course, and outcome vary significantly among patients with cSLE. The onset of cSLE can be at any age during childhood while a diagnosis of cSLE before the age of 5 years is rare and raises a suspicion of monogenic lupus. Childhood-onset systemic lupus erythematosus affects various organs and systems, most frequently presenting with mucocutaneous, musculoskeletal, renal, and neuropsychiatric manifestations. Multiple disease flares can be seen during the disease course. Childhood-onset systemic lupus erythematosus causes significant morbidity and mortality. Children and adolescents with cSLE show higher disease activity and damage, and more aggressive immunosuppressive treatments are needed compared to adultonset SLE. Early diagnosis can be difficult due to the insidious onset with nonspecific symptoms. Disease activity and damage measures aim to ensure an accurate evaluation of disease status. A multidisciplinary approach and individualized disease management are important. Disease management is complex including the control of disease activity, the reduction of flares and damage, and a limitation of drug toxicity while improving the health-related quality of life in patients with cSLE.